2010
DOI: 10.1590/s1519-566x2010000500028
|View full text |Cite
|
Sign up to set email alerts
|

New records of natural enemies of Plutella xylostella (L.) (Lepidoptera: Plutellidae) in Pernambuco, Brazil

Abstract: -We report the occurrence of natural enemies of Plutella xylostela (L.) in organically farmed kale in Pernambuco, Brazil. Seven natural enemies were observed parasitizing or preying on larvae and pupae of P. xylostella -three parasitoids: Cotesia plutellae Kurdjumov (Hym.: Braconidae), Conura pseudofulvovariegata (Becker) (Hym.: Chalcididae) and Tetrastichus howardi (Olliff) (Hym.: Eulophidae), and four predators: Cheiracanthium inclusum (Hentz) (Araneae: Miturgidae), Pheidole sp.Westwood (Hym.: Formicidae), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 7 publications
1
19
0
6
Order By: Relevance
“…Predators often consume leaf material when they have only access to pupae of P. xylostella , which is the least preferred prey. Recent studies have also shown that P. nigrispinus individuals can ingest the contents of phloem and intercellular spaces of plants (Silva‐Torres et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Predators often consume leaf material when they have only access to pupae of P. xylostella , which is the least preferred prey. Recent studies have also shown that P. nigrispinus individuals can ingest the contents of phloem and intercellular spaces of plants (Silva‐Torres et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Westwood (Hymenoptera: Formicidae) and the nymphs and adults of Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) (Silva‐Torres et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of the predator P. nigrispinus , which occurs naturally in brassicas (Silva‐Torres et al. ), together with microbial control seems to be an ideal approach to address the problem of pest developing resistance and attacking the remaining survivors in treated field populations (Johnson et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…2008, cotton (Medeiros et al 2000), eucalyptus (Torres et al 2006), ' Corresponding author, e-mail: amvacarl@gmail.com. tomato (Vivan et al 2002), and crucifers (Brassicaceae; Silva- Torres et al 2010).…”
mentioning
confidence: 99%